Analysis of The Impact of Financial Performance on The Stock Prices of Transportation and Logistics Sector Companies on The Indonesia Stock Exchange for The Period 2020-2024 - Grasella Renya Papuk; Budi Hariono; Hendrik Suhendri (International Journal of Management and Business, 2026)
Financial performance reflects the extent to which a company effectively implements sound financial management practices. The transportation and logistics sector plays a vital role in supporting economic activities, particularly in the distribution of goods and the mobility of people. This study aims to examine the effect of financial performance on the stock prices of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research adopts a quantitative approach using multiple linear regression analysis to test the proposed hypotheses. The data utilized are secondary data obtained from the official IDX website (www.idx.co.id). The population consists of all transportation and logistics companies listed on the IDX, while the sample is selected through purposive sampling based on companies that consistently generated profits during the observation period. The results indicate that Return on Assets (ROA), Current Ratio (CR), Price Earnings Ratio (PER), and Quick Ratio (QR) do not have a significant effect on stock prices, either partially or simultaneously, in transportation and logistics companies listed on the IDX during the 2020–2024 period.